BUDAYA MASYARAKAT OKINAWA DALAM BUKU IKIGAI: THE JAPANESE SECRET TO A LONG AND HAPPY LIFE - Anita Gestiana (Nusantara Hasana Journal, 2024)
Culture that exists in every place or region is different from one another. It is this culture that differs from one society to another that is interesting to discuss, where we can take lessons and value tolerance from existing cultural differences. The book Ikigai: The Japanese Secret to a Long and Happy Life in it discusses the culture of the people of Okinawa, which is the area with the most Centenarians or someone who lives for 100 years in the world. What is the secret of the Longevity of the Okinawan people, this research aims to convey information about the description of Okinawan cultural society depicted in the book. This study uses a qualitative descriptive method with an objective approach. Based on the results of the analysis, it can be concluded that there are several Okinawan cultures that are depicted in the book Ikigai: The Secret to a Long and Happy Life, namely; eating culture, community culture, and active living culture. These three cultures are the secret of the Okinawan people's longevity. By looking at the culture of the Okinawan people, we can take examples and apply them in our daily lives to get a much better and healthier life.